ANALISIS SALURAN PEMASARAN GEMBILI DI KABUPATEN SUKOHARJO - Amalia Nadifta Ulfa; Octaviana Helbawanti; Rosita Dewati; Wahyu Adhi Saputro (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
The community's staple food reliance on rice needs to be reduced through food diversification. Efforts to diversify food can be realized by utilizing local tuber-based foods. One type of tuber that has potential for development is gembili. This research aims to analyze the marketing channels of gembili in Sukoharjo Regency, from the farmer level to the end consumer. This study uses a descriptive qualitative approach to analyze the marketing channels of gembili in Sukoharjo Regency. The respondents of this study consisted of 34 farmers, 7 intermediary traders, 5 wholesalers, 7 retailers, and 20 end consumers who were sampled for the research. Data were collected through in-depth interviews, participatory observations, and document analysis. Data analysis was conducted by analyzing channels, margins, and marketing efficiency. There are 4 marketing channels for gembili in Sukoharjo Regency: Marketing Channel 1: Farmer – Consumer, Marketing Channel 2: Farmer - Collector Trader – Consumer, Marketing Channel 3: Farmer - Collector Trader – Retailer Trader – Consumer, Marketing Channel 4: Farmer - Wholesaler Trader – Retailer Trader – Consumer, with marketing efficiency values for channels 1-4 respectively: 100%, 77.27%, 56.67%, and 57.14%. Efforts are needed to improve farmers' access to accurate and up-to-date market information, infrastructure improvements such as roads and storage facilities must be prioritized to enhance distribution efficiency, and strengthening farmers' institutional capacity is a step towards improving the gembili marketing system.